Tyrosine kinase inhibitors for acute myeloid leukemia: A step toward disease control?. (November 2020) - Megías-Vericat, Juan Eduardo; Ballesta-López, Octavio; Barragán, Eva; Martínez-Cuadrón, David; Montesinos, Pau
Abstract: Dysregulation of tyrosine kinases (TKs) may play a role in leukemogenesis by promoting survival and proliferation of acute myeloid leukemia (AML) cells. In AML, the main TKs mutations are produced in Fms-like tyrosine kinase 3 (FLT3), KIT and Janus kinase (JAK) genes, and with less frequency in BCR-ABL. The striking results with TK Inhibitors (TKIs) therapy in BCR-ABL1 chronic myeloid leukemias has paved the way for its clinical development in AML. However, the AML biology complexity seems to prevent TKI therapy from being proposed as a strong shift in the treatment paradigm and prognosis. While some FLT3 inhibitors have shown efficacy in well-designed studies, an increasing number of AML patients are being treated with TKIs as a new standard of care, compassionate use, or in clinical trials. We will review the current clinical evidence concerning the use of TKIs in different subsets of AML (BCR-ABL1, Core Binding Factor, FLT3 mutated, and FLT3 wild-type) to address the main topics concerning these targeted therapies for AML: 1) optimal place (upfront, relapsed/refractory or maintenance); 2) monotherapy or combination; 3) efficacy in TK mutated versus wild-type patients; 4) differences between selective and multi-targeted TKIs. In the next years, clinical trials and real-world data will help answer these questions and establish the impact of TKIs on outcomes of AML patients. Highlights: FLT3 inhibitors are approved in upfront and relapse/refractory FLT3 -mut AML. 2 ° generation FLT3 inhibitors seems more potent and effective than 1° generation. Future trials should clarify optimal combinations & subsets of potential patients. FLT3 inhibitors could be useful in FLT3- WT setting, but it should be demonstrated.